Multispeed genome diploidization and diversification after an ancient allopolyploidization - Mandáková, Terezie; Pouch, Milan; Harmanová, Klára; Zhan, Shing Hei; Mayrose, Itay; Lysak, Martin A (Molecular ecology, 2017)
Hybridization and genome doubling (allopolyploidy) have led to evolutionary novelties as well as to the origin of new clades and species. Despite the importance of allopolyploidization, the dynamics of postpolyploid diploidization (PPD) at the genome level has been only sparsely studied. The Microlepidieae (MICR) is a crucifer tribe of 17 genera and c. 56 species endemic to Australia and New Zealand. Our phylogenetic and cytogenomic analyses revealed that MICR originated via an intertribal hybridization between ancestors of Crucihimalayeae (n = 8; maternal genome) and Smelowskieae (n = 7; paternal genome), both native to the Northern Hemisphere. The reconstructed ancestral allopolyploid genome (n = 15) originated probably in northeastern Asia or western North America during the Late Miocene (c. 10.6-7 million years ago) and reached the Australian mainland via long-distance dispersal. In Australia, the allotetraploid genome diverged into at least three main subclades exhibiting different levels of PPD and diversity: 1.25-fold descending dysploidy (DD) of n = 15 → n = 12 (autopolyploidy → 24) in perennial Arabidella (3 species), 1.5-fold DD of n = 15 → n = 10 in the perennial Pachycladon (11 spp.) and 2.1-3.75-fold DD of n = 15 → n = 7-4 in the largely annual crown-group genera (42 spp. in 15 genera). These results are among the first to demonstrate multispeed genome evolution in taxa descending from a common allopolyploid ancestor. It is suggested that clade-specific PPD can operate at different rates and efficacies and can be tentatively linked to life histories and the extent of taxonomic diversity.
Keywords: Australia; New Zealand; biologická evoluce; fylogeneze; malování chromozomů; DNA rostlinná; Nový Zéland; Hybridization, Genetic; Genome, Plant; Chromosome Painting; Polyploidy; Austrálie; polyploidie; hybridizace genetická; Gene Rearrangement; genová přestavba; Phylogeny; Biological Evolution; Brassicaceae; DNA, Plant; genom rostlinný